Advances in microwaves. - Young, Leo, 1926-2006 (Academic Press, 1969)
Advances in Microwaves, Volume 4 covers some innovations in the devices and applications of microwaves. This volume contains three chapters and begins with a discussion of the application of microwave phasers and time delay elements as beam steering elements in array radars. The next chapter provides first an overview of the technical aspects and different types of millimeter waveguides, followed by a survey of their application to railroads. The last chapter examines the general mode of conversion properties of nonuniform waveguides, such as waveguide tapers, using converted Maxwell's equatio.